Biomass‐Derived Carbon Materials: Controllable Preparation and Versatile Applications - Wang, Yiliang; Zhang, Mingchao; Shen, Xinyi; Wang, Huimin; Wang, Haomin; Xia, Kailun; Yin, Zhe; Zhang, Yingying (Small (Weinheim an der Bergstrasse, Germany), 2021)
Biomass‐derived carbon materials (BCMs) are encountering the most flourishing moment because of their versatile properties and wide potential applications. Numerous BCMs, including 0D carbon spheres and dots, 1D carbon fibers and tubes, 2D carbon sheets, 3D carbon aerogel, and hierarchical carbon materials have been prepared. At the same time, their structure–property relationship and applications have been widely studied. This paper aims to present a review on the recent advances in the controllable preparation and potential applications of BCMs, providing a reference for future work. First, the chemical compositions of typical biomass and their thermal degradation mechanisms are presented. Then, the typical preparation methods of BCMs are summarized and the relevant structural management rules are discussed. Besides, the strategies for improving the structural diversity of BCMs are also presented and discussed. Furthermore, the applications of BCMs in energy, sensing, environment, and other areas are reviewed. Finally, the remaining challenges and opportunities in the field of BCMs are discussed. Biomass‐derived carbon materials (BCMs) have wide potential applications due to their diverse structures and properties. In this paper, the recent progress in the preparation and applications of BCMs are reviewed. The key processing factors influencing the obtained BCMs, such as, chemical compositions of biomass, carbonization approaches, pretreatment, and activation, are discussed. Finally, the remaining challenges and future directions are discussed.